Management of Vascular Thrombosis in Patients with Thrombocytopenia - Voigtlaender, Minna; Langer, Florian (Hämostaseologie, 2021)
Platelets play critical roles in hemostasis and thrombosis. While low platelet counts increase the risk of bleeding, antithrombotic drugs, including anticoagulants and antiplatelet agents, are used to treat thromboembolic events. Thus, the management of thrombosis in patients with low platelet counts is challenging with hardly any evidence available to guide treatment. Recognition of the underlying cause of thrombocytopenia is essential for assessing the bleeding risk and tailoring therapeutic options. A typical clinical scenario is the occurrence of venous thromboembolism (VTE) in cancer patients experiencing transient thrombocytopenia during myelosuppressive chemotherapy. In such patients, the severity of thrombocytopenia, thrombus burden, clinical symptoms, and the timing of VTE relative to thrombocytopenia must be considered. In clinical practice, distinct hematological disorders characterized by low platelet counts and a thrombogenic state require specific diagnostics and treatment. These include the antiphospholipid syndrome, heparin-induced thrombocytopenia (HIT) and (spontaneous) HIT syndromes, disseminated intravascular coagulation, and paroxysmal nocturnal hemoglobinuria.
Keywords: thrombosis; bleeding; thrombocytopenia; anticoagulation; platelet inhibition